GA Approach in Design Optimisation of a PM Disk Motor - Goga Cvetkovski, Lidija Petkovska, Milan Cundev, Sinclair Gair (Emerald Publishing Limited, 2000)
The paper presents a novel quasi 3-Dimensional Finite Element Method (3D FEM) analysis of a double sided permanent magnet disk motor for electric vehicle. This method is used for a magnetic field analysis of the prototype and the optimal solution. The optimal solution is a product of an optimisation procedure using genetic algorithm as an optimisation tool.
Keywords: Genetic algorithm, optimization, permanent magnet disc motor